Konsepsi Negara Hukum dalam Upaya Penyelesaian Permasalahan Pelanggaran Hak Asasi Manusia di Indonesia - Novario Asca H. (Syntax Literate, 2023)
Indonesia has had serious cases of legal violations. In early 2023, President Jokowi acknowledged the existence of at least 12 (twelve) cases of severe human rights violations in the past, ranging from events related to the G30S/PKI to the Jambo Keuopok incident in Aceh in 2023. This research aims to gain a deeper understanding of the relationship between the concept of a state based on the rule of law and the protection of human rights, as well as how this concept is implemented in real contexts in Indonesia. The method used in this research is a qualitative approach. Research data is obtained through literature reviews, interviews, and observations. Data analysis employs qualitative analysis to identify patterns, trends, and important findings related to the conception of a state based on the rule of law and efforts to address human rights violations in Indonesia. The results of this study show that the human rights legal politics within a democratic rule of law must be promotive, protective, and implementative in order to prevent the abuse of power in the form of human rights violations.